Pengaruh Penggunaan Media Audio Visual Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VII SMP Negeri 1 Sitio-tio Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Mawarni Rajagukguk; Senida Harefa; Grecetinovitria Butar-Butar; Taripar Aripin Samosir; Sandy Ariawan (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
The aim of this research is to determine the positive and significant difference between active learning in Christian Religious Education in students who are taught without the use of Audio Visual Media and active learning in Christian Religious Education in students who are taught using Audio Visual Media in Class VII of SMP Negeri 1 Sitio- tio Samosir Regency 2023/2024 learning year. The method used in this research is a quasi-experimental method with a pre-test and post-test only control group design. The population is all class VII students of SMP Negeri 1 Sitio-tio Samosir Regency for the 2023/2024 academic year, totaling 100 people and the research sample was determined using purposive sampling, namely class VII-B students totaling 32 people. Data was collected using a positive closed questionnaire with 20 items. The results of data analysis show that there is a positive and significant difference in the learning activity of Christian Religious Education in students who are taught without using Audio Visual Media and the Active Learning in Christian Religious Education in students who are taught using Audio Visual Media in Class VII of SMP Negeri 1 Sitio-tio Regency. Samosir 2023/2024 academic year: 1) Data analysis test: a) significant and influence test obtained -tcount= -29.41< -ttabe(=0.05/2=0.025,dk=n-1=3l) = -2.039. The tcount value is in the curve area of ​​rejection of H0 and acceptance of Ha.